2012
DOI: 10.52283/nswrca.ajbmr.20120209a04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microfinance on Poverty Alleviation in Ondo State, Nigeria

Abstract: The paper examines the impact of microfinance on poverty alleviation in Ondo State, Nigeria. The paper is based on a survey of 240 beneficiaries of microcredit loans in Ondo State. The results of the analysis show that most beneficiaries of micro credit loans are educated youth between the age brackets of 18 and 40 years. Many of the beneficiaries utilized their loans to procure durable equipment needed in their small scale enterprises. The results show that loan empowerment has a significant positive effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Also, Tembo (2003) highlighted concerns that valuable aid funds may be diverted to untested and non-viable microfinance programmes instead of being directed toward crucial activities such as education and health. Studies that found no positive impact of microfinance on poverty argue that while it is necessary, microfinancing alone is insufficient for poverty alleviation (Enisan and Oni, 2012). Samer et al (2015) showed that although microfinance is touted as an effective tool for poverty eradication and socio-economic development, its impact is still questioned and varies across countries, differentiating between urban and rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, Tembo (2003) highlighted concerns that valuable aid funds may be diverted to untested and non-viable microfinance programmes instead of being directed toward crucial activities such as education and health. Studies that found no positive impact of microfinance on poverty argue that while it is necessary, microfinancing alone is insufficient for poverty alleviation (Enisan and Oni, 2012). Samer et al (2015) showed that although microfinance is touted as an effective tool for poverty eradication and socio-economic development, its impact is still questioned and varies across countries, differentiating between urban and rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Availability of credit helps diversify household income and smoothens household expenditure, allowing them to absorb economic shocks and fluctuations (Samer et al 2015). Enisan and Oni (2012) emphasised that MFIs are a vehicle through which the poor are empowered. Other studies indicate that universal public education has some roles in preparing youth for basic academic skills and many trade skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, some found no positive effect owing to lack of education, skills, and experience among the target groups (Duong and Izumida 2002). Studies that found no positive impact of microfinance on poverty ague that microfinancing is a necessary but not a sufficient tool towards poverty alleviation (Enisan and Oni 2012). Samer et al (2015) indicate that although microfinancing has been cited as effective poverty eradication and socio-economic development tool, its impact is still questioned and differs from one country to another and even from urban to rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A couple of studies directly investigate the linkage between cultural dimensions and microfinance. Minani (2013) argues that entrepreneurship attitude is highly influenced by cultural values, and that this association is based on the framework of Hofstede's cultural dimensions. The author argues that there is a correlational relationship among culture, entrepreneurship and microfinance, which combined could lead to poverty alleviation.…”
Section: Cultural Dimensions In Indiamentioning
confidence: 99%